Perception of attractiveness of missing maxillary lateral incisors replaced by canines - Souza,Ricardo Alves de (2018)
ABSTRACT Objective: The aim of this study was to evaluate the degree of perception of attractiveness of the smile among dentists, dental students, and lay persons in cases of agenesis of the maxillary lateral incisors replaced by canines for space closure. Methods: A smiling front view extraoral photograph of a 20-year-old woman was digitally altered simulating agenesis and its treatment, by means of: repositioning, reshaping or bleaching the canine, and gingival contour. A questionnaire was distributed to individuals of the three groups (n= 150), with a view to evaluating their degree of esthetic perception. An attractiveness scale was also used, with ‘0’ representing unattractive and ‘10’, very attractive. Results: In the comparative evaluation among all the photographs, the original image obtained the highest level of acceptance. Photograph ‘i’ (agenesis of both lateral incisors treated with reposition and reshaping of the canines) was ranked as the least attractive by the dentists, whereas the student and lay persons ranked photograph ‘f’ (agenesis of both lateral incisors treated with reposition of the canines, gingival contour, bleaching and reshaping) as the worst. Conclusion: The methods of treatment most accepted among the dentists and students were those that involved changes in the gingival contour, whereas among lay persons, they were those that involved only reshaping.